Direct reparation action: case study - Galán Camargo, Viviana (DIXI, 2024)
The research work on the action of reparation in the complex framework of Colombian civil liability takes a case study to analyze and deepen in the evolution of the protection of the so-called weak in the structure of the dynamic burden of proof in Colombia. The specific case was ruled in 2016, after a process that had been initiated in 2007, a situation that affected an entire family group. Colombian jurisprudence and its justice operators are increasingly guarantors of human dignity. In the specific case, despite the time delays, justice was done and the matter was resolved fairly. The Colombian Constitution is based on human dignity, since we are a social state based on the rule of law. The function of the State, among other aspects, is to ensure the quality of life of its associates.